2021
DOI: 10.1084/jem.20201776
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy in lymphatic endothelial cells inhibits T cell–mediated autoimmunity

Abstract: Lymphatic endothelial cells (LECs) present peripheral tissue antigens to induce T cell tolerance. In addition, LECs are the main source of sphingosine-1-phosphate (S1P), promoting naive T cell survival and effector T cell exit from lymph nodes (LNs). Autophagy is a physiological process essential for cellular homeostasis. We investigated whether autophagy in LECs modulates T cell activation in experimental arthritis. Whereas genetic abrogation of autophagy in LECs does not alter immune homeostasis, it induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 83 publications
(128 reference statements)
0
23
0
2
Order By: Relevance
“…Nonetheless, there is ample evidence for immune cell autophagy-related genes dampening inflammation, including diminishing immune cell trafficking. In contrast, while emerging in vivo evidence links autophagy-related genes to a wide array of EC functions, including shear stress-induced homeostasis, angiogenesis, and thrombosis ( Sprott et al., 2019 ; Torisu et al., 2013 ; Vion et al., 2017 ; Verhoeven et al., 2021 ; Harlé et al., 2021 ), knowledge of EC autophagy as a regulator of inflammation is limited. Our findings demonstrated the occurrence and spatiotemporal regulation of autophagy (using GFP-LC3 puncta as readout) in acutely inflamed postcapillary venular ECs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is ample evidence for immune cell autophagy-related genes dampening inflammation, including diminishing immune cell trafficking. In contrast, while emerging in vivo evidence links autophagy-related genes to a wide array of EC functions, including shear stress-induced homeostasis, angiogenesis, and thrombosis ( Sprott et al., 2019 ; Torisu et al., 2013 ; Vion et al., 2017 ; Verhoeven et al., 2021 ; Harlé et al., 2021 ), knowledge of EC autophagy as a regulator of inflammation is limited. Our findings demonstrated the occurrence and spatiotemporal regulation of autophagy (using GFP-LC3 puncta as readout) in acutely inflamed postcapillary venular ECs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic vessels and LECs help to maintain tolerogenic cross‐presentation of self‐antigen and help to limit CD8+ T cell accumulation in the periphery (Hirosue et al, 2014 ; Lane et al, 2018 ). For example, disruption of LEC signaling to the immune environment increases pathogenic Th17 tissue infiltration and further propagates pro‐inflammatory conditions (Harle et al, 2021 ). In the present study, we tested how increased renal lymphatic density prior to the onset of AKI would impact renal outcomes and found that, while the acute response was largely unchanged, the hallmarks of CKD progression such as kidney function and fibrosis were improved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this role in central tolerance, endogenous antigen processing via macroautophagy might also be important for peripheral tolerance and regulatory CD4 + T cell stimulation. Along these lines lymphatic endothelial cells express MHC class II molecules to stimulate regulatory CD4 + T cells (33)(34)(35)(36). Autophagosomes fuse with MIICs in these cells (36).…”
Section: Intracellular Antigen Processing By Macroautophagymentioning
confidence: 99%
“…Along these lines lymphatic endothelial cells express MHC class II molecules to stimulate regulatory CD4 + T cells (33)(34)(35)(36). Autophagosomes fuse with MIICs in these cells (36). Loss of ATG5 compromises regulatory T cell proliferation and phenotype, and results in exacerbated collagen induced arthritis with Th17 infiltrations (36).…”
Section: Intracellular Antigen Processing By Macroautophagymentioning
confidence: 99%
See 1 more Smart Citation